Association between adherence to the Mediterranean diet and self-reported oral manifestations in older adults. - Silva-Gamarra, Moises Elias (2024)
Background: The Mediterranean Diet is very abundant in vitamins that could contribute to the balance in the maintenance of oral cavity health. Therefore, it is necessary to determine the association of adherence to the Mediterranean diet with self-reported oral manifestations in older adults. Methods: The study design was observational, analytical and cross-sectional. It was carried out through a virtual survey in older adults during the year 2022. Validated instruments of adherence to the Mediterranean diet (MEDAS-14) and a self-report on oral manifestations were used, in addition various covariates were evaluated. For the qualitative variables, relative and absolute frequencies were obtained. In the bivariate analysis, the Chi-square statistical test was used. For the association of the qualitative variables and the calculation of the raw and adjusted prevalence ratios, Poisson regression with robust variance was used. Result: It was found that 90.91% of the respondents who maintained a high adherence to the MD did not manifest halitosis. In addition, it was observed that 57.58% who followed a high Mediterranean diet did not manifest dental pain. In the multivariate analysis, a statistically significant association was found between those surveyed who adhered to the MD with certain oral manifestations such as the presence of dental caries, dental pain, halitosis, presence of bleeding, and dental mobility in the crude and adjusted analyzes. Conclusions: Adherence to the Mediterranean diet is related to better health status in an older adult population.